Ketogenic diet and microRNAs: focus on cognitive function - Abrego-Guandique, Diana Marisol; Cione, Erika; Caroleo, Maria Cristina; Bonilla, Diego A.; Cannataro, Roberto (Frontiers in Nutrition, 2025)
Cognition is a mental process of understanding and learning driven by memory. Recent advances in molecular biology and neuroscience have revealed a fascinating interplay between cognitive function and microRNAs (miRNAs). The ketogenic diet (KD) is a low-carbohydrate, high-fat, and adequate-protein diet that triggers the synthesis of ketone bodies, establishing ketosis. Recent and accumulating studies on human and animal models have shown that the KD benefits neurodegenerative diseases, where cognition is affected. The KD can also modulate miRNAs, molecules that are dysregulated in the brains of individuals with Alzheimer’s disease, where cognition is lost. In this mini-review, we provide an overview of the function of miRNAs in neurodevelopment and cognition. We also explore how the KD in human studies can enhance cognitive function and highlight the protective role of microRNAs in neurological conditions.